English file : Pre-intermediate, Workbook with key - Latham-Koenig, Christina; Oxenden, Clive; Hudson, Jane (College teacher); Seligson, Paul (Oxford : Oxford University Press, 2012)
The English File Third Edition Workbook reinforces what is learned in each English File lesson, and can be used as extra practice during class, or set as homework. Now with iChecker, a digital companion to the workbook, suitable for self-testing new grammar, vocabulary and Practical English.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Problems, exercises, etc